PCSK9 affects vascular senescence through the SIRT1 pathway - Yuqin Wang; Shaoqing Cao; Zhangyu Wang; Chengsi Li; Jiangping Ye; Yehong Liu; Tianhui Jin; Yuting Zhou; Wentao Su; Gangjun Zong (Experimental Gerontology)
Age is an independent risk factor for atherosclerotic cardiovascular disease that increases the susceptibility of older adults to vascular intimal thickening, endothelial dysfunction, and thrombosis. However, the mechanism underlying vascular injury is not fully understood. In the present study, the effect of proprotein convertase subtilin-type kexin 9 (PCSK9) inhibitors on the senescent state of human umbilical vein endothelial cells (HUVECs) and on senescent mice and lipopolysaccharides (LPS) were assessed. The senescent state of mice was delayed under PCSK9 inhibitor treatment, and the expression of P16, P21, and P53 proteins in senescent cells was increased because LPS induction stimulated PCSK9 activation. PCSK9 overexpression accelerated cell senescence, activated a large number of oxidative stress pathways, and increased the expression of senescence-related genes (including P16, P21, and P53). In addition, inhibition of the sirtuin 1 (SIRT)1 oxidative stress pathway can attenuate the aging-promoting effects of PCSK9, which are elevated as a result of LPS induction.The SIRT1 activator was more efficient than LPS alone in inducing the expression of senescence-related genes. Therefore, PCSK9 inhibitors can delay the aging of the vascular by reducing cellular SIRT1 levels. Therefore, it can be concluded that PCSK9 inhibition inhibits vascular senescence by reducing the expression of senescent proteins by regulating the SIRT1 pathway.